Phenolic compounds, saponins and alkaloids on cancer progression: emphasis on p53 expression and telomere length - Vakili, Somayeh Afsah; George, Ajay; Ayatollahi, Seyed Abdulmajid; Martorell, Miquel; Ostrander, Elise Adrian; Salehi, Bahare; Martins, Natália; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
Telomere length is correlated with cell proliferation, and cancer cells are characterized by an uncontrolled cell cycle. Being apoptosis one of the checks and balances incorporated into cells cycle, due to its characteristics, cancer cells are able to overcome this process. In particular, the tumour suppressor protein p53 loss or inactivation can lead to activation of telomerase enzyme, which can make cells unable to detect DNA damages that spurs apoptosis. Some bioactive compounds, in particular phenolic compounds, saponins and alkaloids have revealed good abilities to affect p53 expression and indirectly control the telomere length. In this sense, this review gives a key emphasis to the ability of these compounds in blocking cancer progression by acting on p53 expression and controlling telomere length. As main findings, phenolic compounds, saponins and alkaloids interfere with cancer progression by stimulating p53 expression, which can cause pro-apoptotic onset and restrict the anti-apoptotic activity, in addition to preventing telomerase enzyme activity.